Anti-Corruption and Third Party Monitoring - Alejo, Albert (Archīum Ateneo, 2019)
The Bureau of Customs (BOC) is the only Philippine government agency that the Social Weather Station (SWS) has continually ranked as either “very bad” or “execrable” (the bottom of the rankings) for the past decade. In fact, the Asian Development Bank (ADB, 2007) characterizes smuggling in the Philippines as pervasive and abetted by corrupt individuals. Recent analysis by the Citizens’ Customs Action Network (CITIZCAN) finds that, historically, up to 40 centavos for every 1 peso of tax revenue is siphoned by corruption in the BOC…